2021
DOI: 10.3344/kjp.2021.34.3.250
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photobiomodulation on different application points and different phases of complex regional pain syndrome type I in the experimental model

Abstract: Background: Complex regional pain syndrome type I (CRPS-I) consists of disorders caused by spontaneous pain or induced by some stimulus. The objective was to verify the effects of photobiomodulation (PBM) using 830 nm wavelength light at the affected paw and involved spinal cord segments during the warm or acute phase. Methods: Fifty-six mice were randomized into seven groups. Group (G) 1 was the placebo group; G2 and G3 were treated with PBM on the paw in the warm and acute phase, respectively; G4 and G5 trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The study 24 demonstrated that laser (650 nm) inhibited inflammatory response through release of adrenal hormones. According to the study 27 , 780 nm laser with dose of 0.4 J decreased the inflammatory process, down regulated TNF level, however no alteration in IL-6 expression was observed.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The study 24 demonstrated that laser (650 nm) inhibited inflammatory response through release of adrenal hormones. According to the study 27 , 780 nm laser with dose of 0.4 J decreased the inflammatory process, down regulated TNF level, however no alteration in IL-6 expression was observed.…”
Section: Discussionmentioning
confidence: 97%
“…This experimental model provides variation of different therapeutic and pharmacological resources, with the objective of minimizing the inflammatory process 6,7,[13][14][15][16][17][18] . Electrophysical resources, as the photobiomodulation therapy (PBMT), are being largely used in research on different experimental models, such as tendons, peripheral nerve, cutaneous tissue, bones, and muscles [19][20][21][22][23][24] . Moreover, they are being applied for the treatment of acute inflammatory processes, and ensuing resolution of the acute edema 5,6,[25][26][27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation